Perovskite quantum dot for enhancing core-shell anchoring, preparation method thereof and quantum photoelectric device

By pre-coordinating the anion and cation of the perovskite raw material with the active group siloxane, a perovskite quantum dot that enhances core-shell anchoring is solved, and the poor stability of the lead-halide perovskite quantum dots in strict environments is solved. The problem of this method achieves higher stability and density and is suitable for a variety of preparation processes.

CN119220250APending Publication Date: 2024-12-31WUXI UTMOST LIGHT TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202310785208.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

Lead-halogen perovskite quantum dots are difficult to maintain stability under humidity, oxygen environment, ultraviolet light or thermal atmosphere. The core-shell structure isolation effect of the prior art is limited, and ligands are prone to fall off and affect stability.

Method used

By pre-coordinating the anions and cations in the perovskite raw materials with silicones with active groups, a precursor material is formed, and perovskite quantum dots that enhance core-shell anchoring are synthesized to avoid the influence of steric hindrance and enhance the core. The force between the shells and forms a dense shell during the hydrolysis and coating process.

Benefits of technology

It improves the stability and weather resistance of perovskite quantum dots, uniformizes the particle size, simplifies the preparation process, reduces costs, and is suitable for a variety of preparation processes.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119220250A_ABST
    Figure CN119220250A_ABST
Patent Text Reader

Abstract

The invention provides a perovskite quantum dot for enhancing core-shell anchoring, a preparation method of the perovskite quantum dot and a quantum photoelectric device. The perovskite quantum dot has a core-shell structure, the perovskite quantum dot is a halide crystal with an ABX3 type structure, and the method comprises the following steps: pre-coordinating anions and cations at positions A, B and X in a perovskite raw material with a siloxane compound with an active group to form a precursor material, and synthesizing the perovskite quantum dot by using the precursor material, and carrying out coating treatment on the perovskite quantum dot to obtain the enhanced core-shell anchoring perovskite quantum dot. According to the preparation method provided by the invention, a traditional post-treatment SiOx coating process is abandoned, and not only can the mutual anchoring effect between the core and the shell of the perovskite quantum dot be greatly enhanced, so that the stability of the quantum dot is improved, but also the particle size of the quantum dot is more uniform.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of perovskite quantum dot materials, and in particular relates to a perovskite quantum dot with enhanced core-shell anchoring, a preparation method thereof, and a quantum photoelectric device. Background Art

[0002] With the rapid development of science and technology, quantum dot display technology has become one of the most important components of modern optoelectronic products. The popularization and development of optoelectronic products have increasingly higher requirements for many factors such as the display performance, stability and environmental friendliness of materials. In recent years, compared with traditional semiconductor quantum dots, lead halide perovskite quantum dots have gradually become a strong competitor in the display field due to their excellent optical properties, low synthesis cost and environmental friendliness.

[0003] However, lead halide perovskite quantum dot materials are difficult to maintain good stability under harsh conditions such as humidity, oxygen environment, ultraviolet light or thermal atmosphere, which greatly affects their practical application in the display field. In response to this, researchers have conducted a lot of explorations in improving the stability of quantum dots. Among them, the core-shell structure isolates the quantum dots from the external environment by setting a coating layer, which can greatly improve the weather resistance and service life of the quantum dots, and is considered to be one of the effective means to improve the stability of lead halide perovskite quantum dots.

[0004] The prior art discloses a technical solution, in which the quantum dot material is coated with mesoporous silica, which can isolate the quantum dots from direct contact with the external environment and greatly improve its environmental tolerance. However, there are large gaps between the core-shell structure, and the shell material can only play a shielding role but cannot stabilize the lattice. The prior art also discloses another technical solution, in which the surface of the quantum dots is passivated by ligand engineering, which can improve the lattice stability of the quantum dots. However, the ligands are easy to fall off under harsh environments such as light, heat, water and oxygen, and the stability is poor. In the subsequent hydrolysis and coating process, since the shell precursor material is affected by the steric hindrance of the ligand, there is a large amount of independent nucleation, which not only reduces the density of the coating layer, but also affects the luminescence properties of the quantum dots themselves.

[0005] Therefore, it is urgent to propose a method for preparing perovskite quantum dot materials that has a stable effect and a simple method to enhance the interaction between the core-shell structures, so as to improve the stability of lead halide perovskite quantum dots. Summary of the invention

[0006] In view of the shortcomings of the prior art, the present invention aims to provide a perovskite quantum dot with enhanced core-shell anchoring and a preparation method and quantum photoelectric device. The preparation method provided by the present invention abandons the traditional post-processing SiO x The coating process can not only greatly enhance the mutual anchoring effect between the core and shell of perovskite quantum dots, thereby improving the stability of quantum dots, but also make the particle size of quantum dots more uniform.

[0007] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides a method for preparing a perovskite quantum dot with enhanced core-shell anchoring, wherein the perovskite quantum dot has a core-shell structure, and the perovskite quantum dot is a halide crystal with an ABX3 type structure, wherein A is any one of a monovalent cation of methylamine, methylamidine or cesium, B is a divalent lead ion or a stannous ion, and X is a halogen anion, and the method comprises the following steps:

[0009] The anions and cations at positions A, B, and X in the perovskite raw material are pre-coordinated with a siloxane compound having an active group to form a precursor material, the precursor material is used to synthesize perovskite quantum dots, and the perovskite quantum dots are coated to obtain the enhanced core-shell anchored perovskite quantum dots.

[0010] First, the present invention prepares a precursor by pre-coordinating the anions and cations constituting the raw materials of the perovskite with siloxanes having active groups, so that the active groups and ions can fully interact with each other and avoid any steric hindrance. Then, the perovskite quantum dots are synthesized, so that the surface anions and cations can be firmly combined with the siloxanes having active groups, and the interaction between the core and shell after hydrolysis and coating can be enhanced, which can avoid the problem of lattice coarsening caused by ligand shedding, and thus help to improve the stability and weather resistance of the structure. Compared with the technical solution disclosed in the prior art that only anion coordination is performed, only anion coordination has the following problems: on the one hand, the active sites of the surface siloxane are insufficient; on the other hand, only pre-coordinating anions will cause a large difference in the reaction activity of anions and cations, which is not conducive to the synthesis of quantum dots, and at the same time breaks the surface ligand balance, affecting the optical properties and stability of quantum dots. The present invention uses anions and cations to pre-coordinate with siloxanes having active groups at the same time to avoid the above problems;

[0011] Secondly, since the siloxane compound is added in the form of pre-coordination, there is almost no SiO x Independent nucleation has no effect on the luminescence properties of quantum dots. In addition, in theory, the ions on the surface of each quantum dot can be used as SiO x Active sites for nucleation and growth are formed, so that the particle size of the quantum dot core-shell structure is more uniform. At the same time, the siloxane with active groups is pre-coordinated with anions and cations, and can act as a ligand itself, without the need to add additional ligands. On the one hand, it can save costs, and on the other hand, it also simplifies the post-processing operation process;

[0012] Finally, after the precursor material is synthesized into perovskite quantum dots in the above preparation method, its surface has firmly bonded siloxane groups. In the subsequent coating process, the surface siloxane is hydrolyzed to form a shell, and additional coating materials are added to increase the density of the shell. At the same time, the above preparation method is applicable to various perovskite quantum dot preparation processes such as hot injection method and room temperature method, indicating that it has good universality; and the present invention can use siloxane compounds with different groups and different chain lengths to customize and control the coordination strength, and has good adjustability; and the preparation method is simple and easy to scale up, which is conducive to industrialization.

[0013] Preferably, when the siloxane compound having active groups is pre-coordinated with the cations at the A and B positions, the active groups in the structure of the siloxane compound having active groups include any one of carboxyl groups, sulfonate groups or phosphate groups or a combination of at least two of them, preferably sulfonate groups.

[0014] In the present invention, by preferably using the siloxane compound having the above-mentioned active groups, during the coordination process between the siloxane compound and the cation, the siloxane compound has a suitable coordination strength and the cation has a higher reactivity in the synthesis stage.

[0015] Preferably, when the siloxane compound having an active group is pre-coordinated with the cations at the A and B positions, the siloxane compound having an active group includes any one of 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropyl(dimethoxy)silane or silane PEG acid, or a combination of at least two thereof, preferably 3-mercaptopropyltriethoxysilane.

[0016] Preferably, when the siloxane compound having an active group is pre-coordinated with the anion at the X position, the active group in the structure of the siloxane compound having an active group includes an amino group.

[0017] In the present invention, by preferably using the siloxane compound having the above-mentioned active groups, during the coordination process between the siloxane compound and the anion, the siloxane compound has a suitable coordination strength and the anion has a higher reactivity in the synthesis stage.

[0018] Preferably, when the siloxane compound having an active group is pre-coordinated with the anion at the X position, the siloxane compound having an active group includes any one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyldimethoxymethylsilane, 3-aminopropylmethyldiethoxysilane, N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane, 3-aminopropyltri(methoxyethoxyethoxy)silane, [3-(1,3-dimethylbutenyl)aminopropyl]triethoxysilane or N-[2-(N-vinylbenzylamino)ethyl]-3-aminopropyltrimethoxysilane or a combination of at least two thereof, preferably 3-aminopropyltriethoxysilane.

[0019] Preferably, the molar ratio of the siloxane compound having an active group to the cation at the A position is (0.05-10):1, preferably (1-7):1, for example, it can be 0.05:1, 0.08:1, 0.1:1, 0.2:1, 0.5:1, 0.8:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, etc.

[0020] In the present invention, by adjusting the molar ratio of the siloxane compound with active groups to the cation at the A position, a strong pre-coordination strength and good reactivity are formed. If the molar ratio is too low, the coordination degree will be poor, otherwise it will affect the reactivity and increase the cost.

[0021] Preferably, the molar ratio of the siloxane compound having an active group to the cation at the B position is (0.05-10):1, preferably (1-7):1, for example, it can be 0.05:1, 0.08:1, 0.1:1, 0.2:1, 0.5:1, 0.8:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, etc.

[0022] In the present invention, by adjusting the molar ratio of the siloxane compound with active groups to the cation at the B position, a strong pre-coordination strength and good reactivity are formed. If the molar ratio is too low, the coordination degree will be poor, otherwise it will affect the reactivity and increase the cost.

[0023] Preferably, the molar ratio of the siloxane compound having an active group to the anion at the X position is (0.05-10):1, preferably (1-7):1, for example, it can be 0.05:1, 0.08:1, 0.1:1, 0.2:1, 0.5:1, 0.8:1, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, etc.

[0024] In the present invention, by adjusting the molar ratio of the siloxane compound with active groups to the anion at the X position, a strong pre-coordination strength and good reactivity are formed. If the molar ratio is too low, the coordination degree will be poor, otherwise it will affect the reactivity and increase the cost.

[0025] Preferably, the temperature for pre-coordination of the siloxane compound having an active group with the anions and cations at positions A, B, and X is 25 to 150°C, preferably 60 to 120°C, for example, it can be 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, etc.

[0026] Preferably, the pre-coordination time of the siloxane compound having an active group with the anions and cations at positions A, B, and X is 5 to 120 min, preferably 10 to 60 min, for example, it can be 5 min, 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, 65 min, 70 min, 75 min, 80 min, 85 min, 90 min, 95 min, 100 min, 105 min, 110 min, 115 min, 120 min, etc.

[0027] In the present invention, the temperature and time of pre-coordination are adjusted to allow the anions and cations to be fully coordinated with the siloxane.

[0028] Preferably, the pre-matching method includes but is not limited to a hot injection method or a room temperature mixing method, preferably a hot injection method.

[0029] Preferably, the reaction temperature of the hot injection method is 60-230°C, preferably 100-160°C, for example, it can be 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 180°C, 200°C, 210°C, 220°C, 230°C, etc.

[0030] Preferably, the method of synthesizing perovskite quantum dots includes a room temperature method and a hot injection method.

[0031] Preferably, the reaction temperature of the hot injection method is 60-230°C, preferably 100-160°C, for example, it can be 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, 130°C, 135°C, 140°C, 145°C, 150°C, 155°C, 160°C, 180°C, 200°C, 210°C, 220°C, 230°C, etc.

[0032] Preferably, the coating treatment is obtained by hydrolyzing a silicon source and / or an aluminum source.

[0033] Preferably, the silicon source includes any one of tetramethoxysilane, tetraethoxysilane, hexamethyldisilazane, hexamethyldisiloxane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyldimethoxymethylsilane, 3-aminopropylmethyldiethoxysilane, N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane, 3-aminopropyltri(methoxyethoxyethoxy)silane, [3-(1,3-dimethylbutenyl)aminopropyl]triethoxysilane or N-[2-(N-vinylbenzylamino)ethyl]-3-aminopropyltrimethoxysilane or a combination of at least two thereof, preferably tetramethoxysilane.

[0034] Preferably, the aluminum source includes any one of aluminum isopropoxide, aluminum sec-butoxide, aluminum n-butoxide, aluminum tert-butoxide, aluminum triethoxide, trimethylaluminum, tributylaluminum, basic aluminum acetate, aluminum dihydrogen phosphate or sodium aluminate, or a combination of at least two thereof, preferably aluminum sec-butoxide.

[0035] Preferably, the total addition amount of the silicon source and / or aluminum source is 0.1 to 5 mmol / mL, preferably 0.3 to 0.5 mmol / mL, for example, it can be 0.1 mmol / mL, 0.2 mmol / mL, 0.3 mmol / mL, 0.32 mmol / mL, 0.35 mmol / mL, 0.38 mmol / mL, 0.4 mmol / mL, 0.42 mmol / mL, 0.45 mmol / mL, 0.48 mmol / mL, 0.5 mmol / mL, 0.8 mmol / mL, 1 mmol / mL, 2 mmol / mL, 3 mmol / mL, 4 mmol / mL, 5 mmol / mL and the like.

[0036] In the present invention, by adjusting the total amount of silicon source and / or aluminum source added, the hydrolysis process has a higher reaction activity, and the reaction rate is controlled to improve the coating density.

[0037] Preferably, the temperature of the coating treatment is 25-80°C, preferably 40°C, for example, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, etc.

[0038] Preferably, the humidity of the coating treatment is 30-60% rh, preferably 40-50% rh, for example, it can be 30% rh, 35% rh, 40% rh, 42% rh, 45% rh, 48% rh, 50% rh, 52% rh, 55% rh, 58% rh, 60% rh, etc.

[0039] Preferably, the coating treatment time is 0.5 to 24 h, preferably 6 to 8 h, for example, it can be 0.5 h, 0.5 h, 0.8 h, 1 h, 2 h, 4 h, 6 h, 7 h, 8 h, 10 h, 14 h, 18 h, 20 h, 22 h, 24 h, etc.

[0040] In a second aspect, the present invention provides a perovskite quantum dot with enhanced core-shell anchoring, wherein the perovskite quantum dot with enhanced core-shell anchoring comprises an outer shell, and a perovskite quantum dot core disposed in the outer shell, wherein the perovskite quantum dot core is bonded and anchored to the outer shell, and the perovskite quantum dot with enhanced core-shell anchoring is prepared by the method for preparing perovskite quantum dots with enhanced core-shell anchoring according to the first aspect.

[0041] In a third aspect, the present invention provides a quantum optoelectronic device, comprising the enhanced core-shell anchored perovskite quantum dots according to the second aspect.

[0042] Compared with the prior art, the present invention has the following beneficial effects:

[0043] The present invention provides a method for preparing perovskite quantum dots with enhanced core-shell anchoring, which firstly pre-coordinates the anions and cations constituting the perovskite raw materials with siloxanes having active groups to prepare a precursor, so that the active groups and ions fully interact with each other and avoid any steric hindrance, and then synthesizes the perovskite quantum dots, so that the surface anions and cations can be firmly combined with the siloxanes having active groups, thereby enhancing the interaction between the core and shell after hydrolysis and coating, thereby facilitating the improvement of the stability and weather resistance of the structure;

[0044] Secondly, since the siloxane compound is added in the form of pre-coordination, there is almost no SiO x Independent nucleation has no effect on the luminescence properties of quantum dots. In addition, in theory, each ion on the surface of a quantum dot can be used as a SiO xActive sites for nucleation and growth are formed, so that the particle size of the quantum dot core-shell structure is more uniform. At the same time, the siloxane with active groups is pre-coordinated with anions and cations, and can act as a ligand itself, without the need to add additional ligands. On the one hand, it can save costs, and on the other hand, it also simplifies the post-processing operation process;

[0045] Finally, the above preparation method is applicable to various perovskite quantum dot preparation processes such as hot injection method and room temperature method, indicating that it has good universality; and the present invention can customize the coordination strength by using siloxane compounds with different groups and different chain lengths, and has good adjustability; and the preparation method is simple and easy to scale up, which is conducive to industrialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 A schematic diagram of the synthesis and coating process of perovskite quantum dots provided in Example 1;

[0047] Figure 2 Performance test diagram of perovskite quantum dots provided in Example 1;

[0048] Figure 3 Performance test diagram of perovskite quantum dots provided in Example 2;

[0049] Figure 4 Performance test diagram of perovskite quantum dots provided in Example 3;

[0050] Figure 5 Performance test diagram of perovskite quantum dots provided in Example 4;

[0051] Figure 6 Performance test diagram of perovskite quantum dots provided in Example 5;

[0052] Figure 7 Performance test diagram of perovskite quantum dots provided in Example 6;

[0053] Figure 8 Performance test diagram of perovskite quantum dots provided in Example 7;

[0054] Fig. 9 Performance test diagram of perovskite quantum dots provided in Example 8;

[0055] Fig.10 Performance test diagram of perovskite quantum dots provided for comparative example 1;

[0056] Fig.11 Performance test diagram of perovskite quantum dots provided for comparative example 2;

[0057] Fig.12 Performance test diagram of perovskite quantum dots provided for comparative example 3;

[0058] Fig.13 Performance test diagram of perovskite quantum dots provided for comparative example 4. DETAILED DESCRIPTION

[0059] The technical solution of the present invention is further described below by combining the accompanying drawings and specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0060] Example 1

[0061] This embodiment provides a perovskite quantum dot with enhanced core-shell anchoring and a preparation method thereof. The structural formula of the perovskite quantum dot is FAPbBr3, such as Figure 1 As shown, it includes the following steps:

[0062] (1) 0.054 g of formamidine acetate was added to a mixture of 0.8 mL of 3-mercaptopropyltriethoxysilane and 5 mL of 1,3,5-trimethylbenzene, the mixture was evacuated and heated to 60° C., and the mixture was reacted for 10 min to be used as a FA precursor.

[0063] (2) 0.102 g of lead acetate trihydrate was added to a mixture of 0.4 mL of 3-mercaptopropyltriethoxysilane and 1 mL of octadecene, the mixture was evacuated and heated to 120° C., and the mixture was reacted for 30 min to be used as a Pb precursor.

[0064] (3) 0.432 g of dioctadecyl dimethyl ammonium bromide was mixed with 1 mL of 3-aminopropyltriethoxysilane and 1 mL of 1,3,5-trimethylbenzene, and the mixture was placed on a hot plate at 120 °C for 30 min to be used as a Br precursor.

[0065] (4) Precursors (1) and (2) and 10 mL of 1,3,5-trimethylbenzene were mixed and added into a three-necked flask. After evacuating the flask at room temperature for 10 min, nitrogen was introduced and the temperature was raised to 120°C.

[0066] (5) Use a syringe to extract the Br precursor in (3) and inject it into the reaction system (4). After reacting for 5 seconds, cool it to room temperature in an ice water bath.

[0067] (6) After the reaction, 30 mL of ethyl acetate was added to the crude solution, and the mixture was centrifuged at 8000 rpm for 5 min. The precipitate was dispersed with 10 mL of toluene and centrifuged again at 5000 rpm for 5 min. The supernatant was collected and placed in a sample bottle for later use.

[0068] (7) 3 mL of the supernatant in step (6) was placed in a 20 mL glass sample bottle, 150 μL of tetramethoxysilane was added, and the solution was placed in a reaction environment at 40° C. and 45% rh for 8 h. The solution was then taken out and centrifuged at 8000 rpm for 5 min.

[0069] (8) Dry the precipitate in a vacuum oven at 40 °C for 4 h, grind it evenly with a mortar, and place it in a sample bottle for later use.

[0070] Example 2

[0071] The difference between this embodiment and embodiment 1 is that the structural formula of the perovskite quantum dots is CsPbBr 1.2 I 1.8 , add 0.1753 g of cesium carbonate in step (1) to a mixed solution of 0.8 mL of 3-mercaptopropyltriethoxysilane and 1 mL of octadecene, evacuate and heat to 60° C., react for 10 min, and use it as a Cs precursor; in step (3), mix 0.1728 g of dioctadecyldimethylammonium bromide, 0.0682 g of potassium iodide, 1 mL of 3-aminopropyltriethoxysilane, and 1 mL of 1,3,5-trimethylbenzene, place on a hot plate at 120° C. until it is completely dissolved into a transparent solution, and use it as a Br / I precursor. The rest is the same as in Example 1.

[0072] Example 3

[0073] The difference between this embodiment and embodiment 1 is that 150 μL of tetramethoxysilane in step (7) is replaced by 172.5 μL of aluminum sec-butoxide, and the rest is the same as embodiment 1.

[0074] Example 4

[0075] The difference between this embodiment and embodiment 1 is that the perovskite quantum dot synthesis steps (4)-(6) are replaced by: the precursors of (1)-(3) and 10 mL of dimethyl sulfoxide are mixed evenly, the mixed solution is injected into 30 mL of toluene solution, and then centrifuged at 5000 rpm for 5 min, and dispersed with 10 mL of toluene again, and placed in a sample bottle for standby use. The rest is the same as embodiment 1.

[0076] Example 5

[0077] The difference between this embodiment and embodiment 1 is that in step (1), 0.8 mL of 3-mercaptopropyltriethoxysilane is replaced by 6.5 μL, and the reaction is carried out at room temperature for 5 min; in step (2), 0.4 mL of 3-mercaptopropyltriethoxysilane is replaced by 3.5 μL, and the reaction is carried out at room temperature for 5 min; in step (3), 1 mL of 3-aminopropyltriethoxysilane is replaced by 8.5 μL, and the reaction is carried out at room temperature for 5 min. The rest is the same as in embodiment 1.

[0078] Example 6

[0079] The difference between this embodiment and embodiment 1 is that in step (1), 0.8 mL of 3-mercaptopropyltriethoxysilane is replaced by 6.5 μL, and the reaction is carried out at 150° C. for 120 min; in step (2), 0.4 mL of 3-mercaptopropyltriethoxysilane is replaced by 3.5 μL, and the reaction is carried out at 150° C. for 120 min; in step (3), 1 mL of 3-aminopropyltriethoxysilane is replaced by 8.5 μL, and the reaction is carried out at 150° C. for 120 min. The rest is the same as in embodiment 1.

[0080] Example 7

[0081] The difference between this embodiment and embodiment 1 is that 44.5 μL of tetramethoxysilane is added in step (7), and the mixture is placed in a reaction environment at room temperature and 30% rh for reaction for 0.5 h. The rest is the same as embodiment 1.

[0082] Example 8

[0083] The difference between this embodiment and embodiment 1 is that 2230 μL of tetramethoxysilane is added in step (7), and the mixture is placed in a reaction environment at 80° C. and 60% rh for 24 h. The rest is the same as embodiment 1.

[0084] Comparative Example 1

[0085] This comparative example provides a perovskite quantum dot having a structural formula of FAPbBr3 and a preparation method thereof, which comprises the following steps:

[0086] (1) Mix 0.432 g of dioctadecyl dimethyl ammonium bromide with 1 mL of 1,3,5-trimethylbenzene and heat on a hot plate at 120°C until the mixture is completely dissolved into a transparent solution for use as a Br precursor.

[0087] (2) 0.054 g of formamidine acetate, 0.102 g of lead acetate trihydrate, 0.617 g of 4-dodecylbenzenesulfonic acid and 10 mL of 1,3,5-trimethylbenzene were mixed and added to a three-necked flask. The mixture was evacuated at room temperature for 10 min, and then nitrogen was introduced and the temperature was raised to 120°C.

[0088] (3) Use a syringe to extract the Br precursor in (1) and inject it into the reaction system (2). After reacting for 5 seconds, cool it to room temperature in an ice water bath.

[0089] (4) After the reaction, 30 mL of ethyl acetate was added to the crude solution, and the mixture was centrifuged at 8000 rpm for 5 min. The precipitate was dispersed with 10 mL of toluene and centrifuged again at 5000 rpm for 5 min. The supernatant was collected and placed in a sample bottle for later use.

[0090] (5) 3 mL of the supernatant in (4) was placed in a 20 mL glass sample bottle, 150 μL of tetramethoxysilane was added, and the solution was placed in a reaction environment at 40° C. and 45% rh for 8 h. After that, the solution was taken out and centrifuged at 8000 rpm for 5 min.

[0091] (6) Dry the precipitate in a vacuum oven at 40 °C for 4 h, grind it evenly with a mortar, and place it in a sample bottle for later use.

[0092] Comparative Example 2

[0093] The difference between this comparative example and Example 1 is that in step (4), in addition to the (1)-(2) precursors and 10 mL of 1,3,5-trimethylbenzene, 0.617 g of 4-dodecylbenzenesulfonic acid needs to be added, and the rest is the same as Example 1.

[0094] Comparative Example 3

[0095] The difference between this comparative example and Example 1 is that in step (7), 150 μL of tetramethoxysilane is not added, and the hydrolysis reaction is directly carried out. The other steps are the same as those in Example 1.

[0096] Comparative Example 4

[0097] The difference between this comparative example and Example 1 is that steps (1)-(2) are omitted, 0.617 g of 4-dodecylbenzenesulfonic acid is additionally added in step (4), and the rest is the same as Example 1.

[0098] Test conditions

[0099] The perovskite quantum dots provided in Examples 1 to 8 and Comparative Examples 1 to 4 were subjected to aging and stability tests, and the test methods are as follows:

[0100] The prepared perovskite quantum dot powder was mixed with film-making glue at a mass ratio of 1:100, encapsulated with a water-oxygen barrier film (10-2), cured by ultraviolet light, and cut into 50x50cm films for testing.

[0101] Dry heat aging (HT): The sample film was placed in an oven at 85°C for aging;

[0102] Blue light aging (BL): The sample film is placed under a 1500nits, 450nm LED light source for aging;

[0103] Room temperature (CW): place the sample membrane at room temperature and pressure for aging;

[0104] After aging for different times, take the corresponding samples, cool them to room temperature and pressure, and use a fluorescence tester to test the aging and stability of the sample membranes. The test results are as follows: Figure 2-Figure 13 As shown:

[0105] The data results of Examples 1-4 show that Figure 2-Figure 5 As shown, the method of synthesizing perovskite quantum dots by pre-formulated precursors and then improving the density by hydrolysis coating can form a strong core-shell bond and a higher shell density, which can significantly improve the stability of the aging process. This method is applicable to both hot injection and room temperature methods, to both green quantum dots and red quantum dots, and to both silicon source coating and aluminum source coating.

[0106] Comparison of the data results of Example 1 with those of Examples 5 and 6 shows that Figure 2 , Figure 6 and Figure 7 As shown, in the pre-preparation precursor stage, lower concentration, lower temperature and shorter reaction time cannot make siloxane fully coordinated with the precursor material, and it is difficult to play the role of ligand. The synthesized quantum dots are too large, the luminescence is weak and the stability is poor; while higher concentration, higher temperature and longer reaction time will cause siloxane to hydrolyze prematurely, affecting the normal quantum dot synthesis and post-processing coating process.

[0107] Comparison of the data results of Example 1 with those of Examples 7 and 8 shows that Figure 2 , Figure 8 and Fig. 9 As shown, in the hydrolysis and coating stage, less feed, lower temperature and humidity, and shorter reaction time resulted in insufficient siloxane hydrolysis, and both the core-shell firmness and shell density failed to reach a good state, which seriously affected the stability; while excessive feed, higher temperature and humidity, and longer reaction time, on the one hand, coarsened the quantum dot lattice and affected the luminescence performance, and on the other hand, the particle size after coating was larger, the granularity was obvious after film making, and the uniformity was poor.

[0108] Comparison of the data results of Example 1 and Comparative Example 1 shows that Figure 2 and Fig.10 As shown, the quantum dots were co-regulated by normal ligand synthesis and coated by post-processing. The shell density was poor, the core and shell were not firm, and the stability of the aging process did not meet the standards.

[0109] Comparison of the data results of Example 1 and Comparative Example 2 shows that Figure 2 and Fig.11 As shown, if a ligand is added normally during the synthesis using a pre-combined precursor, the steric hindrance of the ligand will inhibit the reaction activity, resulting in a low concentration of the generated quantum dots, making it difficult to meet the initial brightness standards, and having a negative impact on the surface coordination of the precursor, resulting in poor stability. This indicates that siloxane is used for pre-combination and no additional ligand needs to be added.

[0110] Comparison of the data results of Example 1 and Comparative Example 3 shows that Figure 2 and Fig.12As shown, no additional silicon source / aluminum source is added during the hydrolysis stage. Although a firmly bonded core-shell structure can be formed, the shell layer has poor density and cannot fully meet the stability requirements.

[0111] Comparison of the data results of Example 1 and Comparative Example 4 shows that Figure 2 and Fig.13 As shown, only anion pre-coordination is performed, the optical properties of quantum dots are slightly deficient, and there are fewer siloxane hydrolysis active sites on the surface of quantum dots, the coating density is poor, and the stability is poor.

[0112] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing perovskite quantum dots with enhanced core-shell anchoring, characterized in that: The perovskite quantum dot has a core-shell structure, and the perovskite quantum dot is a halide crystal with an ABX3 type structure, wherein A is any one of a monovalent cation of methylamine, methylamidine or cesium, B is a divalent lead ion or a stannous ion, and X is a halogen anion. The method comprises the following steps: The anions and cations at positions A, B, and X in the perovskite raw material are pre-coordinated with a siloxane compound having an active group to form a precursor material, the precursor material is used to synthesize perovskite quantum dots, and the perovskite quantum dots are coated to obtain the enhanced core-shell anchored perovskite quantum dots.

2. The method according to claim 1, characterized in that When the siloxane compound with active groups is pre-coordinated with the cations at the A and B positions, the active groups in the structure of the siloxane compound with active groups include any one of carboxyl groups, sulfonate groups or phosphate groups or a combination of at least two of them, preferably sulfonate groups.

3. The method according to claim 2, characterized in that When the siloxane compound having an active group is pre-coordinated with the cations at the A and B positions, the siloxane compound having an active group includes any one of 3-mercaptopropyltrimethoxysilane, 3-mercaptopropyltriethoxysilane, 3-mercaptopropyl(dimethoxy)silane or silane PEG acid, or a combination of at least two thereof, preferably 3-mercaptopropyltriethoxysilane.

4. The method according to claim 1, characterized in that: When the siloxane compound having an active group is pre-coordinated with the anion at the X position, the active group in the structure of the siloxane compound having an active group includes an amino group.

5. The method according to claim 4, characterized in that When the siloxane compound having an active group is pre-coordinated with the anion at the X position, the siloxane compound having an active group includes any one of 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyldimethoxymethylsilane, 3-aminopropylmethyldiethoxysilane, N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane, 3-aminopropyltri(methoxyethoxyethoxy)silane, [3-(1,3-dimethylbutenyl)aminopropyl]triethoxysilane or N-[2-(N-vinylbenzylamino)ethyl]-3-aminopropyltrimethoxysilane or a combination of at least two thereof, preferably 3-aminopropyltriethoxysilane.

6. The method according to any one of claims 1 to 5, characterized in that The molar ratio of the siloxane compound having an active group to the cation at the A position is (0.05-10):1, preferably (1-7):1; Preferably, the molar ratio of the siloxane compound having an active group to the cation at the B position is (0.05-10):1, preferably (1-7):1; Preferably, the molar ratio of the siloxane compound having an active group to the anion at the X position is (0.05-10):1, preferably (1-7):

1.

7. The method according to any one of claims 1 to 6, characterized in that The temperature for pre-coordinating the siloxane compound having active groups with the anions and cations at the A, B, and X positions is 25 to 150° C., preferably 60 to 120° C.; Preferably, the pre-coordination time of the siloxane compound having active groups with the anions and cations at the A, B, and X positions is 5 to 120 minutes, preferably 10 to 60 minutes.

8. The method according to any one of claims 1 to 7, characterized in that The method of synthesizing perovskite quantum dots includes a room temperature method and a hot injection method; Preferably, the coating treatment is obtained by hydrolyzing a silicon source and / or an aluminum source; Preferably, the silicon source includes any one of tetramethoxysilane, tetraethoxysilane, hexamethyldisilazane, hexamethyldisiloxane, 3-aminopropyltrimethoxysilane, 3-aminopropyltriethoxysilane, 3-aminopropyldimethoxymethylsilane, 3-aminopropylmethyldiethoxysilane, N-(β-aminoethyl-γ-aminopropyl)methyldimethoxysilane, 3-aminopropyltri(methoxyethoxyethoxy)silane, [3-(1,3-dimethylbutenyl)aminopropyl]triethoxysilane or N-[2-(N-vinylbenzylamino)ethyl]-3-aminopropyltrimethoxysilane or a combination of at least two thereof, preferably tetramethoxysilane; Preferably, the aluminum source includes any one of aluminum isopropoxide, aluminum sec-butoxide, aluminum n-butoxide, aluminum tert-butoxide, aluminum triethoxide, trimethylaluminum, tributylaluminum, basic aluminum acetate, aluminum dihydrogen phosphate or sodium metaaluminate, or a combination of at least two thereof, preferably aluminum sec-butoxide; Preferably, the total addition amount of the silicon source and / or aluminum source is 0.1 to 5 mmol / mL, preferably 0.3 to 0.5 mmol / mL; Preferably, the coating treatment temperature is 25 to 80°C, preferably 40°C; Preferably, the humidity of the coating treatment is 30-60% rh, preferably 40-50% rh; Preferably, the coating treatment time is 0.5 to 24 hours, preferably 6 to 8 hours.

9. A perovskite quantum dot with enhanced core-shell anchoring, characterized in that: The enhanced core-shell anchored perovskite quantum dots include an outer shell and a perovskite quantum dot core disposed in the outer shell, wherein the perovskite quantum dot core is bonded and anchored to the outer shell, and the enhanced core-shell anchored perovskite quantum dots are prepared by the method for preparing enhanced core-shell anchored perovskite quantum dots according to any one of claims 1-8.

10. A quantum optoelectronic device, characterized in that: The quantum optoelectronic device comprises the enhanced core-shell anchored perovskite quantum dots according to claim 9.